Enterprise information systems : 15h International Conference, ICEIS 2013, Angers, France, July 4-7, 2013, Revised Selected Papers - Cordeiro, Jose; Maciaszek, Leszek A.; Filipe, Joaquim; Hammoudi, Slimane (Lecture Notes in Business Information Processing, 2014)
This book contains substantially extended and revised versions of the best papers from the 15th International Conference on Enterprise Information Systems, ICEIS 2013, held in Angers, France, in July 2013. The 29 full and two invited papers included in this volume were carefully reviewed and selected from 321 submissions. They reflect state-of-the-art research focusing mainly on real-world applications and highlight the benefits of information systems and technology for industry and services, thus connecting academia with the world of real enterprises. The topics covered are: databases and information systems integration, artificial intelligence and decision support systems, information systems analysis and specification, software agents and Internet computing, human-computer interaction, and enterprise architecture.